Precursor and pressure dependent 3D graphene: A study on layer formation and type of carbon material - Saheed, M.S.M. (Elsevier Ltd, 2017)
The variation and structural properties of interconnected and freestanding 3D graphene grown in atmospheric (AP) and low pressure (LP) conditions with varying precursor concentrations (7–14) is reported for the first time. LP grown 3D graphene at low precursor concentration (7 vol) shows turbostratic signature whereas AP grown 3D graphene indicates a double layer signature in the same condition. The 2D band peaks splitting evaluation through Lorentzian fitting shows the distinct variations in the number of layers grown for each precursor concentrations. Extensive Raman analysis of the grown samples revealed the existence of disordered plane stacking of graphene layers, which decreases as the precursor concentration increases. In contrast, AP grown 3D graphene shows no disordered layers for any precursor concentration. The increase in a number of layers (2 to 5) of 3D graphene grown in both AP and LP conditions co-influenced by precursor concentrations is validated by TEM. Interestingly, it was discovered that both 3D graphene grown in different conditions exhibit sp2 ring carbon material. Thus, control over growth kinetics by varying the precursor concentration in different chamber pressures allows for total manipulation of the number of layers of 3D graphene deposited on the template nickel catalyst. © 2017 Elsevier B.V.